PERFORMANCE ANALYSIS OF INTERNAL MODEL CONTROLLER - JUMAIN, IMRAN (Universiti Teknologi Petronas, 2005)
The topic chooses for the Final Year Project is Performance Analysis of an Internal Mode! Controller (IMC). The project is conducted by comparing the performances between the Internal Model Controller and the conventional PID Controller. A lot of studies of various controllers have been done. This is why the project is conducted where to have better understanding on the implementation of Internal Model Controller to any system. The purpose of the research is to present more evidence of IMC; some ofthe advantages and limitation. The project has been conducted using the UTP pilot plant 6. The temperature loop (TIC 634) controlled by the control valve (FY631) is used throughout the project. This plant system currently utilizes the conventional PID Controller. The empirical modeling technique (process reaction curve) has been chose to be the modeling technique throughout the project period based on the analysis conducted during the first semester ofthe project. The generated model becomes important when the author need to design and implement the controller in order to minimize the error of the system. In other words, the controller is implemented to ensure the output response reaches its steady state value without experiences large overshoot and longer settling time. By comparing all the result and analysis, it shows that IMC has a better result in tuning. Only one variable, Xis tuned for IMC compared with PID which required tuning three (3) variables; proportional, integral and derivative. IMC can also be tuned to improve the performance ofthe system.